OPTIMALISASI PENGELOLAAN KEUANGAN DESA UNTUK PEMBANGUNAN BERKELANJUTAN : STUDI KASUS DESA PASIRTALAGA - Gun Gumilar, Gun; Sugiarto, Dimas; Elyas, Ahmad Mudzaki; Atika, Ayu (Governance, 2025)
The Village Fund in Indonesia launched in 2015 through the policy of Village Law No. 6/2014 provides a strong impetus for villages to independently manage their financial resources to achieve inclusive, prosperous, and environmentally friendly development. This study aims to analyse how village financial management can be optimised to support sustainable development.  The theory used is sustainable development which consists of three main pillars, namely economic, social, and environmental, developed by the Brundtland Commission (1987). This research uses a qualitative approach with a case study method that aims to explore efforts to optimise village financial management in supporting sustainable development in Pasirtalaga Village. The case study was chosen because it provides an in-depth description of the local dynamics of village financial management that is unique and specific to the context of Pasirtalaga Village.  The results showed that optimised village financial management can improve the efficiency of allocating funds to development projects that can improve the economy, increase social welfare and maintain sustainability.